(untitled) (Canadian Dermatology Today, 2022)
Psoriasis is a chronic, immune-mediated, genetic inflammatory skin disease that occurs in 2-3% of the Canadian population, which is comparable in incidence and prevalence to Europe and the USA. It begins in childhood in almost a third of patients and the prevalence increases in a linear pattern from age 1 to age 18. The incidence continues to increase from the 2nd decade reaching a peak in the latter half of the 6th decade. The global incidence of psoriasis has increased over the past 30 years in both adults and children, especially in North America and Western Europe. As illustrated in this case, psoriasis is associated with comorbidities, such as hypertension, obesity, impaired glucose tolerance, hyperlipidemia, arthritis, and inflammatory bowel disease. These comorbidities occur in twice as many patients under the age of 20 with psoriasis as those without. The first line of treatment for mild-to-moderate psoriasis is topical therapy, which also complements systemic therapies in more severe disease.